PENGARUH AUDITOR SWITCHING, UKURAN PERUSAHAAN, SPESIALISASI INDUSTRI KAP, DAN CLIENT IMPORTANCE PADA KUALITAS AUDIT - Udayanti, Ni Kadek Sri; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 20 No 2 (2017), 2017)
This study was purpose to determine the effect of auditor switching, firm size, audit firm industry specialization , and client importance on audit quality. The population of this research is all manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2013-2015. The total of manufacturing companies listed on the Stock Exchange in 2013-2015 as many as 143 companies . Based on the results of purposive sampling with criteria established acquired 89 companies in the sample. Observation period for 3 years  from 2013 to 2015, in order to obtain total observation as much as 267 companies. Data analysis used  multiple linear regression . Results of the test showed that firm size and audit firm industry specialization affects on audit quality. Auditor Switching and client importance had no effect on audit quality.
Keywords: audit quality, auditor switching, firm size, audit firm industry specialization, client importance